Evaluación Heurística de aplicaciones para Android con soporte para múltiples tamaños de pantalla: Caso de Estudio - Romaina Acevedo, Juan Carlos Eduardo (2018)
Heuristic evaluation of applications built for mobile devices has different implications than their desktop (web or OS) based counterparts. The singularities of the Android platform, due especially to the vast range of devices with different specifications of hardware, make the testing scenarios not easy to cover, and are sometimes overlooked. The present work studies the implications of doing heuristic evaluation of mobile applications that support multiple screen sizes and resolutions, and proposes an adaptation of the standard, with regards to the problems and challenges that these tasks entail. It also presents a validation of the adaptation using a realworld case study.